1996
DOI: 10.1183/09031936.96.09091831
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 expression by lung cancer cell lines: effects of upregulation by cytokines on the interaction with LAK cells

Abstract: I IC CA AM M--1 1 e ex xp pr re es ss si io on n b by y l lu un ng g c ca an nc ce er r c ce el ll l l li in ne es s: : e ef ff fe ec ct ts s o of f u up pr re eg gu ul la a--t ti io on n b by y c cy yt to ok ki in ne es s o on n t th he e i in nt te er ra ac ct ti io on n w wi it th h L LA AK K c ce el ll ls s Eur Respir J., 1996, 9, 1831-1838

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…For example, adhesion molecules are implicated in the cellto-cell contact between tumour cells and LAK or NK cells. Thus, a recent report demonstrated that ICAM-1 was expressed spontaneously by NSCLC cell lines and by IFN-γ-stimulated SCLC cell lines [172]. Together with other cell adhesion molecules, ICAM-1 could facilitate the binding of tumour cells to LAK cells.…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…For example, adhesion molecules are implicated in the cellto-cell contact between tumour cells and LAK or NK cells. Thus, a recent report demonstrated that ICAM-1 was expressed spontaneously by NSCLC cell lines and by IFN-γ-stimulated SCLC cell lines [172]. Together with other cell adhesion molecules, ICAM-1 could facilitate the binding of tumour cells to LAK cells.…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…In the past few years several new targets have been identified for NSC lung cancer, most notably EGFR and VEGF, and it is hoped that they will translate to improved treatment outcomes. [49][50][51] Since CD54 is also up-regulated on a majority of NSC lung tumor cell lines investigated in this and other studies, 21,22 it might represent another important therapeutic target. When administered to SCID/NSC lung tumor mice, UV3 slowed the growth of palpable tumors, both alone and in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its demonstrated anti-tumor activity, UV3 has been chimerized (cUV3) to reduce its immunogenicity in humans. 17 Since CD54 expression is up-regulated in many different types of cancer cells, [18][19][20][21][22] we hypothesized that UV3 would have activity against other CD54 1 tumors as well. We have now expanded the testing of UV3 to include human breast, prostate, NSC lung, and pancreatic tumor cell lines.…”
mentioning
confidence: 99%
“…ICAM-1 is up-regulated on the surface of a variety of lymphomas, pancreatic, bladder and lung carcinomas and/or their local vascular network [99]. A cyclic peptide, cyclo-(1,12)-PenITDGEATDSGC (cLABL), derived from the Idomain of the L subunit of leukocyte function associated antigen-1 LFA-1 integrin has been shown the binding affinity to the D1 domain of ICAM-1 [100].…”
Section: Cell Adhesion Molecule Receptor Targeted Therapymentioning
confidence: 99%